Professional Autonomy. Key Competence for Teachers in Commercial Education - Araya Muñoz, María Isabel (2012)
The way in which the teaching autonomy is materialized, considered as part of the path traveled by the teaching community on their way to become owners of the disciplinary knowledge and the required pedagogical competencies to practice their role has motivated this paper.  For success, Commercial Education requires the urgent transformation of the teaching role and the development of key competences to promote interdisciplinary integration, academic and administrative leadership and the use of contemporary pedagogies.  The level of awareness reached by the teaching group about the impact of the learning that is promoted within the educational context will allow the empowerment of the knowledge that comes from the relationship between theory and practice-key element for professional autonomy.